STRATEGI PENGAMANAN MELALUI CRIME PREVENTION THROUGH ENVIRONTMENT DESIGN DI RUTAN KELAS IIB KRUI - Riduwan Al-Farisi; Syahrial Yuska (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Security strategy in correctional facilities is a crucial aspect in preventing potential threats to safety and order. This study aims to analyze the implementation of Crime Prevention Through Environmental Design (CPTED) as a strategic approach to security at Class IIB Krui Detention Center. CPTED emphasizes the role of physical environment design and management in reducing crime opportunities and enhancing natural surveillance. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that the security strategy at Class IIB Krui Detention Center has adopted CPTED principles such as natural surveillance, access control, and maintenance to create a secure and orderly environment. However, several challenges remain, including infrastructure limitations, human resource shortages, and budget constraints, which affect the effectiveness of the implementation. The study recommends capacity building for officers, utilizing surveillance technology, and improving spatial arrangements and physical facilities to optimally support CPTED principles. When properly applied, CPTED can serve as a strategic solution in creating a more preventive and efficient security system within correctional settings.